Evolving techniques for gastrointestinal endoscopic hemostasis treatment. (3rd May 2016) - Ghassemi, Kevin A.; Jensen, Dennis M.
ABSTRACT: With mortality due to gastrointestinal (GI) bleeding remaining stable, the focus on endoscopic hemostasis has been on improving other outcomes such as rebleeding rate, need for transfusions, and need for angiographic embolization or surgery. Over the past few years, a number of devices have emerged to help endoscopically assess and treat bleeding GI lesions. These include the Doppler endoscopic probe, hemostatic powder, and over-the-scope clip. Also, new applications have been described for radiofrequency ablation. In this article, we will discuss these evolving tools and techniques that have been developed, including an analysis of their efficacy and limitations.